2002
DOI: 10.3354/meps238101
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of species diversity patterns of free-living marine nematodes

Abstract: Nematode species diversity was analysed for 55 data points ranging from local studies to large-scale faunal surveys. Multiple regression analysis uses latitude, investigated area, sampling effort and depth as independent variables. Species diversity in a biotope (or α-diversity) is about twice as high in the deep sea, while the main source of diversity in shallow waters is heterogeneity of biotopes (β-diversity). For sites deeper than 100 m, regional species richness shows a unimodal (hump-shaped) latitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 34 publications
3
41
0
1
Order By: Relevance
“…2009). For nematodes, the results are equivocal, and whether latitude or depth primarily determines the observed patterns is a matter of discussion (Lambshead et al 2000, Mokievsky & Azovsky 2002, Lambshead & Boucher 2003. For example, compilation of the published data did not reveal any prominent latitudinal gradients for shallow water free-living marine nematodes in the southern hemisphere, whereas the samples collected specifically along the coast of Chile between 18 and 42°S showed that sandy beach nematode fauna follows the classic latitudinal gradient (Boucher 1990, Lee & Riveros 2011.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…2009). For nematodes, the results are equivocal, and whether latitude or depth primarily determines the observed patterns is a matter of discussion (Lambshead et al 2000, Mokievsky & Azovsky 2002, Lambshead & Boucher 2003. For example, compilation of the published data did not reveal any prominent latitudinal gradients for shallow water free-living marine nematodes in the southern hemisphere, whereas the samples collected specifically along the coast of Chile between 18 and 42°S showed that sandy beach nematode fauna follows the classic latitudinal gradient (Boucher 1990, Lee & Riveros 2011.…”
mentioning
confidence: 87%
“…These findings may also shed some light on the 'latitude or depth' discussion related to the leading gradients in meiofaunal diversity (Lambshead et al 2000, Mokievsky & Azovsky 2002. Both factors are important but affect different diversity components, and the relative importance of latitude drops but that of depth increases in the deepest areas.…”
Section: Relative Role Of Diversity Componentsmentioning
confidence: 98%
See 2 more Smart Citations
“…There have been many studies investigating diversity patterns, with special emphasis on how biodiversity varies with depth and latitude (Mokievsky & Azovsky 2002;Gage et al 2004;Renaud et al 2009), most of which have identified an increase in diversity with water depth through the bathyal zone (Rex 1981;Levin et al 2001). On the other hand, the latitudinal gradient in species richness is a well-known biogeographical pattern in terrestrial ecology, where there is an observed increase in species diversity from high to low latitudes (from the poles to the tropics) (Pianka 1966;Gray et al 1997;Gaston & Blackburn 2000).…”
Section: Introductionmentioning
confidence: 99%